A Study on Managing Processes by Statistical Process Control - Karan, Soumitra (Prabandhan: Indian Journal of Management, 2009)
Statistical Process Control works upon process - not on output and is an effective system which primarily needs the basic understanding of production processes in order to detect and curb process variations that may affect the quality of the end product or service - the prime cause of customer dissatisfaction and defection. Initially SPC eradicates the assignable causes of variation by local actions and then a comprehensive long term planning is required to reduce chance cause variations gradually by management involvement and actions to get outputs of predictable, controllable and acceptable variations which fall within customers’ specification limits. On going process status is resolved through SPC tools commonly known as control charts. In this article, Average - Range (X - R) chart is discussed in detail as it is well-accepted by both academicians and practitioners. To shoot process outputs with in the specification limits following acceptance - rejection criteria is fundamentally a goal post concept. The aim of SPC is further extended to minimize chance causes and gradually shrinks control limits and specification limits towards the central target assigned by the customers. This streamlines processes towards the journey of excellence intrinsically i.e. the state of art to bridge the quality planning gap between actual and desired quality achievement through adoption of SPC to deliver attractive products with cost-effectiveness.